Diarrhea in solid organ transplant recipients. Issue 4 (August 2015) - Angarone, Michael; Ison, Michael G.
Abstract : Purpose of review: Diarrhea is a common complaint in the solid organ transplant recipient. Unlike the immune-competent patient, diarrhea in an organ transplant recipient may result in dehydration, increased toxicity of medications, and rejection. There is a wide range of causes for diarrhea in transplant recipients, but the most common causes are Clostridium difficile infection, cytomegalovirus, and norovirus. This review will focus on new epidemiology data as to the cause of diarrhea in the transplant population. Recent findings: Recent data have identified C. difficile, cytomegalovirus, and norovirus as important causes of diarrhea in this population, and management should be focused on these causes. Newer diagnostic platforms (such as PCR) are being evaluated, which may help in identification of the cause of diarrhea. Summary: New epidemiologic data and new testing techniques offer an opportunity for research into better testing strategies for transplant patients with diarrhea. These newer testing strategies may offer better insight into the cause of diarrhea and more appropriate treatment for this illness.